A Study on the Effects of Gluteal Muscle Activation on the Electromyography of Lower Limb Muscles in Young Male Patients With Patellofemoral Pain Syndrome - Wu Yue; Ren Shuang; Huang Hongshi; Ao Yingfang; Gou Bo (Orthopaedic Surgery)
ABSTRACT Objective Patellofemoral pain syndrome (PFPS) is a common knee issue, and hip joint function significantly affects knee health. Gluteus activation exercises are a promising treatment for PFPS. This study aims to investigate the impact of gluteal muscle activation exercises on the muscle involvement and movement patterns of young male patients with PFPS. Methods Our study was a randomized controlled clinical trial study from June 2020 to December 2021, included 18 young male patients with PFPS, randomly divided into two groups: the gluteus activation group (GAG) and control group (CON), with nine cases in each group. The GAG underwent gluteal muscle activation exercises for 40 min per session, three times per week, for 6 weeks; the CON received no intervention. At baseline and after 6 weeks, the integrated electromyography (IEMG), contribution rates (CRs), and activation times (ATs) of the gluteus maximus (GM), vastus medialis (VM), rectus femoris (RF), vastus lateralis (VL), biceps femoris (BF), and semitendinosus (ST) muscles of the affected lower limb during stair‐climbing exercise were assessed. Additionally, the explosive power (EP) of the lower limbs and the visual analog scale (VAS) pain value of the knee joint were evaluated. Paired sample t‐tests and independent sample t‐tests were used to compare the differences within and between groups. Results After 6 weeks, the GAG showed a significant increase in the IEMG of GM by 118 ± 67.09 μVs compared to CON (p < 0.05), and an increase in the CR of the GM by 6.75% (p < 0.05). Additionally, the AT of the GM and BF was significantly reduced (p < 0.05), and the lower limb EP increased by 14.66% compared to the CON (p < 0.05). Concurrently, there was a very significant reduction in the knee VAS pain score (p < 0.01). The CON exhibited no significant changes in the EMG indices of the lower limbs, EP, and VAS before and after the 6 weeks (p > 0.05). Conclusion A 6‐week gluteal muscle activation training program for patients with PFPS can adjust and optimize the IEMG, CR, and firing order of the lower limb muscle groups, enhance EP, and alleviate pain.